2003
DOI: 10.1097/01.mat.0000084105.01116.9e
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experiment with a Newly Developed Double Balloon, Double Lumen Catheter for Extracorporeal Life Support Vascular Access

Abstract: Recently, venovenous extracorporeal life support (VVECLS) using a double lumen catheter has been clinically used to avoid neurologic complications in the treatment of respiratory failure for neonates. However, recirculation, which is a limiting factor for oxygen delivery, still exists, and thus it does not contribute to oxygenation of the patient. We developed a newly designed double lumen catheter with a double balloon (DBDL) catheter for ECLS vascular access and performed two animal preliminary experiments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…For example, the report of the Dialysis Outcomes and Practice Patterns Study (DOPPS) work group showed that the types of vascular access used in maintenance hemodialysis patients were quite different in the US, Japan, and European countries (6). The ratio found in the present study was compatible with the ratio documented in original clinical papers from Japan and European countries (7,8).…”
Section: Discussionsupporting
confidence: 92%
“…For example, the report of the Dialysis Outcomes and Practice Patterns Study (DOPPS) work group showed that the types of vascular access used in maintenance hemodialysis patients were quite different in the US, Japan, and European countries (6). The ratio found in the present study was compatible with the ratio documented in original clinical papers from Japan and European countries (7,8).…”
Section: Discussionsupporting
confidence: 92%
“…A variation in the SvO 2 method has been described both in animal models 19 and in neonates 9 receiving venovenous ECMO via dual-lumen cannulae, with recirculation assessed in the neonate study at the end of each ECMO run when the subjects could tolerate suspension of sweep gas flow. 9 SvO 2 was first measured with the sweep gas flow turned off ("SvO 2 ") and again with sweep gas set at 100% oxygen ("SQO 2 ").…”
Section: Estimating the Amount Of Recirculationmentioning
confidence: 99%
“…6, 2005 / pp. 609-616 The effects of pulsatile versus non-pulsatile extracorporeal circulation on the pattern of coronary artery blood flow during cardiac arrest (ECLS) is the device used in emergency cases to substitute a extracorporeal circulation in open heart surgery, cardiac arrest or in acute cardiopulmonary failure (1,5,6). It preserves the patient's life by providing the adequate oxygen supply and blood flow to the vital organs.…”
Section: Artificial Heart and Cardiac Assist Devicesmentioning
confidence: 99%